The Intensity of Watching Korean Dramas with Premarital Sex Behaviors of Female Students at X University Yogyakarta - Suci Musvita Ayu; luluk Fitri Abdiati (Gaster, 2021)
Based on Indonesia Demographic and Health Survey from 2017, female adolescents aged 15-24 claimed to have committed premarital sex during dating. 64% held hands, 30% kissing, 17% hugging, 5% petting, and 2% have sexual intercourse experience. Those who view Korean dramas in long-term and high frequented can develop imagination and greater experience with these activities (dating and the activities). This study aims to find the relationship between Korean dramas viewing and the premarital sex behavior of female students at University X Yogyakarta. The method in this study used quantitive with cross-sectional research design. The sample of this research were 179 respondents, taken by accidental sampling. Data collected with questionnaires. The data analysis used the Chi-square test. The Result intensity of Korean dramas viewing was high with 83,8%. The stage of female students' premarital sex behavior was held hands (30,2%). Chi-square statistic test showed that p-value was 0,595 (p > 0,05) and PR value was 0,941 at CI 95% (0,765 – 1,159). There was no relationship between Korean dramas viewing and female students' premarital sex behavior at University X Yogyakarta.